Effect of nonreciprocity on frictional torque acting on a nanoparticle - Chai, Siao Yang (Nanyang Technological University, 2022)
In this thesis, we had derived a general formula that described the frictional torque acting on a gyrotropic nanoparticle near a nonreciprocal medium using fluctuation-dissipation theorem (FDT). The expression is a generalisation of previous results in isotropic vacuum to anisotropic vacuum where rotational symmetry is broken due to the presence of nonreciprocal medium. It was tested by the constructions of numerical plots for a model consisting of a InSb (gyrotropic) or a SiC (isotropic) particle, and a class of topological insulator known as Chern insulator in the non-dispersive limit, which is well-known for exhibiting QAHE. We saw that an initially stationary particle can undergo spontaneous rotation as long as there is a finite temperature difference. Besides that, the ensuing torque behaviour has an oscillatory dependence on the position of the particle with respect to the insulator. We have also studied how the temperature differences, Chern numbers and magnetic field strengths have their bearings on the resultant torque behaviour. Most interestingly, our nonreciprocal settings had led to exotic dynamics such as time-reversal asymmetries and enhancements of particle's rotation in thermal equilibrium with the anisotropic vacuum.